Embedding of superparamagnetic iron oxide nanoparticles into membranes of well-defined poly(ethylene oxide)-block-poly(ε-caprolactone) nanoscale magnetovesicles as ultrasensitive MRI probes of membrane bio-degradation. Issue 30 (10th July 2019) - Hannecart, Adeline; Stanicki, Dimitri; Vander Elst, Luce; Muller, Robert N.; Brûlet, Annie; Sandre, Olivier; Schatz, Christophe; Lecommandoux, Sébastien; Laurent, Sophie
Abstract : The present study reports the preparation of PEO- b -PCL polymer vesicles via a nanoprecipitation method and the loading of hydrophobically coated USPIO into the membrane of these nanovesicles, whose thickness was measured precisely by SANS. Abstract : The present study reports the preparation of poly(ethylene oxide)- block -poly(ε-caprolactone) (PEO- b -PCL) polymer vesicles via a nanoprecipitation method and the loading of two different size hydrophobically coated ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles (a magnetic core size of 4.2 nm and 7.6 nm) into the membrane of these nanovesicles, whose thickness was measured precisely by small angle neutron scattering (SANS). Spherical nano-assemblies with a high USPIO payload and a diameter close to 150 nm were obtained as confirmed by dynamic light scattering (DLS), transmission electron microscopy (TEM) and cryo-TEM. The vesicular structure of these hybrid nano-assemblies was confirmed by multi-angle light scattering (MALS) measurements. Their magnetic properties were evaluated by T 1 and T 2 measurements (20 and 60 MHz) and by nuclear magnetic relaxation dispersion (NMRD) profiles. The size of USPIO entrapped in the membranes of PEO- b -PCL vesicles has a strong impact on their magnetic properties. It affects both their longitudinal and their transverse relaxivities and thus their magnetic resonance imaging (MRI) sensitivity. Acid-catalyzed hydrolysis of the PCL membrane also influences their relaxivities as shown by measurements carried out at pH 7 vs. pH 5. This property was used to monitor the membrane hydrolytic degradation in vitro, as a proof of concept of potential monitoring of drug delivery by nanomedicines in vivo and non-invasively, by MRI.